Water and poverty in China's Yellow river basin - Ahmed, Akhter; Wang, Jinxia; Bhaskar, Anjor; Quabili, Wahid (International Food Policy Research Institute, 2010)
Rapid economic growth in the Yellow River Basin (YRB) of China has put intense demands on Yellow River waters. By far the largest user of water resources is the agricultural sector, accounting for 80 percent of total withdrawals—with industrial, urban, and rural domestic sectors sharing the remaining 20 percent. Demands for irrigation have surpassed available resources for decades. Given that water is critical for agricultural production, access to water is a key determinant of welfare of the rural poor in the YRB region for whom agriculture is the main source of livelihood.